First Language Contribution to Second Language Learning and Foreign Language Development In The Town of Lhokseumawe - ahyar, Juni; Yusri Ibrahim, Mohd; Husin, Muzir (Jurnal Indonesia Sosial Sains, 2023)
Teachers recognize that different language teaching methods are appropriate for different situations. The social context and desire of immigrant adults to learn English as a Second Language (ESL) requires that the educational approach be different from that of other students. who must pass the school exams. SFL's contributions to language teaching focus on providing descriptions of the language as it is actually used and suggesting ways to help learners understand its usage. In other words, they tend to focus on the expected learning outcome rather than the learning process. This helps researchers find contextual features that influence the grammatical features of the language under study. We analyze the ups and downs of language use in cultural and situational contexts and how language function development responds to the functional demands of the situation. Here are some facts that can be used as evidence of conversational behavior development and change. The context of the spoken language is relatively stable, making it easier for non-fluent speakers to share information. Fluent speakers are more free or flexible than non-fluent speakers when introducing context, and the use of dynamic speech by NS and NNS has been shown to help maintain conversational flow. I'm here. At the lower level, acknowledgments and repairs are often used as dynamic functions. These two types of functionality have more limited functionality than the prompt and instruction types that occur at higher levels. This opens the opportunity for tender negotiations